Answers

The Brainliest Answer!
  • Brainly User
2016-03-28T01:20:22+05:30

Solution:


3x2² - x - 2 = 0


Break the equation


⟹ 3x2^2 - 3x + 2x - 2 = 0


⟹ 3x(x - 1) + 2(x - 1) = 0


⟹ (x - 1)(3x + 2) = 0


To get the answer we have to use the zero-product rule 


x - 1 = 0 or, 3x + 2 = 0


⟹ x = 1 or x = -2/3


Simplify the equation


x = -2/3, 1.


1 5 1
2016-03-28T13:01:09+05:30
We have,

3x2² - x - 2 = 0


⟹ 3x2² - 3x + 2x - 2 = 0


⟹ 3x(x - 1) + 2(x - 1) = 0


⟹ (x - 1)(3x + 2) = 0

x - 1 = 0 or, 3x + 2 = 0

    We get,

⟹ x = 1 or x = -2/3

∴ Values of x = -2/3, 1

1 5 1